2018
DOI: 10.3177/jnsv.64.445
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sarcopenia and Its Relationship with Nutritional State and Quality of Life in Patients with Digestive Diseases

Abstract: This study aimed to clarify the prevalence of sarcopenia, which is characterized by loss of skeletal muscle mass and strength, and its relationship with nutritional state and quality of life (QOL) in patients with digestive diseases. This study enrolled 303 patients (187 men and 116 women with a median age of 70 y) having digestive diseases. Diseases were gastrointestinal in 99 patients, biliary/pancreatic in 93, and hepatic in 111. Skeletal muscle cross-sectional area was measured by abdominal computed tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
2
14
0
1
Order By: Relevance
“…As male patients had significantly higher baseline hemoglobin levels with a higher SMI we additionally analyzed the association between sarcopenia and hemoglobin levels using the sex specific cut-offs, and found that patients with sarcopenia had lower baseline hemoglobin levels independent of sex. This is in line with published data on sarcopenia ( 21 ). A link between chronic inflammation and sarcopenia has been proposed ( 14 , 22 ).…”
Section: Discussionsupporting
confidence: 93%
“…As male patients had significantly higher baseline hemoglobin levels with a higher SMI we additionally analyzed the association between sarcopenia and hemoglobin levels using the sex specific cut-offs, and found that patients with sarcopenia had lower baseline hemoglobin levels independent of sex. This is in line with published data on sarcopenia ( 21 ). A link between chronic inflammation and sarcopenia has been proposed ( 14 , 22 ).…”
Section: Discussionsupporting
confidence: 93%
“…Multivariable proportional odds logistic analysis indicated that malaise, edema of the limbs, peripheral sensory neuropathy, pruritus, and dry skin were significant factors for reducing the EQ-5D-5L utility value. Several reports support the present results, highlighting the association between adverse events and decreased QOL [8,[19][20][21]. Secondary analysis using proportional odds logistic regression did not show a significant association between QOL and cancer type or anticancer drugs.…”
Section: Discussionsupporting
confidence: 84%
“…Limb edema is a characteristic finding in patients with malnutrition. Onishi et al [19] reported that malnutrition in cancer patients is associated with decreased QOL. Additionally, Hershman et al, using the Functional Assessment of Cancer Therapy/Gynecologic Oncology Group-Neurotoxicity, reported that QOL scores decreased from 37.5 to 28.7 post-treatment (P = 0.0002).…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia, low muscle mass and low muscle strength result in a deteriorated clinical course of liver disease. [ 25 , 26 ] In addition, low muscle mass is associated with impaired HRQOL among patients with liver disease. Although we could not identify an association between ASMI and HRQOL, hand grip tended to be positively associated with the activity domain.…”
Section: Discussionmentioning
confidence: 99%